The Role of Butirprost® as an Adjuvant in Enhancing the Effect of Antibiotics in Patients Affected by Chronic Bacterial Prostatitis: A Randomized Prospective Trial - Felice Crocetto; Armando Calogero; Michele Santangelo; Agostino Fernicola; Filippo Varlese; Benito Fabio Mirto; Fabio Machiella; Alfonso Falcone; Giovanni Pagano; Fabrizio Dinacci; Gaetano Giampaglia; Domenico Varriale; et al. (Medicina)
Bacterial prostatitis (BP) is a common prostatic infection characterized by pain and urinary symptoms, often with negative bacterial cultures from prostatic secretions. It affects young and older men bimodally and impacts quality of life (QoL) significantly. Background and Objectives: Treatment typically involves antibiotics, but a multimodal approach with additional nutraceuticals may enhance outcomes. This study aimed to assess the efficacy of Butirprost® in association with fluoroquinolones in patients with chronic bacterial prostatitis (CBP). Materials and Methods: Patients diagnosed with prostatitis (positive Meares–Stamey test and symptom duration > 3 months) at the University of Naples “Federico II”, Italy, from March 2024 to July 2024 were included in this study. All patients underwent bacterial cultures. Patients were randomized into two groups: Group A received antibiotics plus Butirprost® (sodium hyaluronate plus Plantago major) for one month, while Group B received antibiotics alone. International Prostatic Symptoms Score (IPSS) and National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) questionnaires were administered at baseline and at 15 and 30 days. Results: Out of 60 patients (Group A: 30, Group B: 30), Group A showed significant improvement in IPSS and NIH-CPSI scores at 15 and 30 days compared to Group B. Notable improvements were observed in pain, urinary symptoms, and QoL. Conclusions: The administration of Butirprost® along with fluoroquinolones resulted in a significant improvement in pain, urinary symptoms, and quality of life along with improvements in both IPSS and NIH-CPSI scores, in patients affected by chronic bacterial prostatitis compared with fluoroquinolones alone.